Cardiovascular disease, cancer and mortality among people with type 2 diabetes and alcoholic or non-alcoholic fatty liver disease hospital admission - Wild, Sarah H.; Walker, Jeremy J.; Morling, Joanne R.; McAllister, David A.; Colhoun, Helen; Farran, Bassam; McGurnaghan, Stuart; McCrimmon, Rory; Read, Stephanie H.; Sattar, Naveed; Byrne, Christopher D. (American Diabetes Association, 2018)
OBJECTIVE: To describe associations between alcoholic fatty liver disease (ALD) or non-alcoholic fatty liver disease (NAFLD) hospital admission and cardiovascular disease (CVD), cancer, and mortality in people with T2DM. RESEARCH DESIGN AND METHODS: We performed a retrospective cohort study using linked population-based routine data from the diabetes register, hospital, cancer and death records for people aged 40-89 years, diagnosed with T2DM in Scotland 2004-2013 who had one or more hospital admission records. Liver disease and outcomes were identified using International Classification of Diseases codes. We estimated hazard ratios from Cox proportional hazards models, adjusted for key risk factors (aHRs). RESULTS: There were 134,368 people with T2DM (1707 with ALD and 1452 with NAFLD) with mean follow-up of 4.3 years for CVD and 4.7 years for mortality. Among people with ALD, NAFLD or without liver disease hospital records respectively there were: 378, 320 and 21,873 CVD events, 268, 176 and 15,101 cancers and 724, 221 and 16,203 deaths. For ALD and NAFLD respectively, aHRs (95% CIs) compared to the group with no record of liver disease were: 1.59 (1.43, 1.76) and 1.70 (1.52, 1.90), for CVD; 40.3 (28.8, 56.5) and 19.12(11.71 31.2), for hepatocellular cancer (HCC); 1.28 (1.12, 1.47) and 1.10 (0.94, 1.29) for non-HCC cancer; 4.86 (4.50, 5.24) and 1.60 (1.40, 1.83) for all-cause mortality. CONCLUSIONS: Hospital records of ALD or NAFLD are associated, to varying degrees, with increased risk of CVD, cancer and mortality in people with T2DM.